Prevalence, Genotypic Characteristics and Antibiotic Resistance of Listeria monocytogenes From Retail Foods in Bulk in Zhejiang Province, China - Zhang, Yunyi; Dong, Shilei; Chen, Honghu; Chen, Jiancai; Zhang, Junyan; Zhang, Zhen; Yang, Yong; Xu, Ziyan; Zhan, Li; Mei, Lingling (Frontiers in Microbiology, 2019)
Listeria monocytogenes is an important foodborne pathogen causing public concern. A total of 3354 retail foods in bulk were sampled and screened for L. monocytogenes. Seventy-three (2.2%) samples including 21 ready-to-eat (RTE) foods and 52 raw foods were confirmed positive for L. monocytogenes. Sushi and salmon sashimi occupied the top two slots in RTE foods with relatively high presence rate of 12.9% and 6.9%, respectively. Meanwhile, L. monocytogenes was found to be distributed unequally in raw foods; the presence rates in raw meat (3.5%) and poultry (3.8%) were significantly higher than that in raw seafood (1.3 %). Notably, L. monocytogenes was not detected in raw freshwater food. The L. monocytogenes isolates belonged to four serotypes, 1/2a, 1/2b, 1/2c and 4b, with the most prevalent serotype being 1/2a (47.9%). Eighteen sequence types (STs) and eighteen virulence types (VTs) containing four newly assigned VTs (VT180, VT181, VT182 and VT183) were determined via multilocus sequence typing (MLST) and multi-virulence-locus sequence typing (MVLST). Among the 73 L. monocytogenes isolates, 23 (31.5%) belonged to epidemic clones (ECs) including ECI, ECIV, ECV, ECVI, ECVIII and ECXI among which ECV was predominant. Antibiotic susceptibility tests revealed a high resistance rate (11.0%) to tetracycline. Moreover, we identified the distribution patterns of virulence genes of four Listeria pathogenicity islands (LIPI) in L. monocytogenes isolates. prfA, hly, plcA, plcB, mpl, actA genes in LIPI-1 and inlA, inlB, inlC, inlJ genes in LIPI-2 were detected in approximately all L. monocytogenes isolates. The distribution of both LIPI-3 genes and LIPI-4 genes exhibited association with lineage and ST. LIPI-4 genes were present exclusively in ST87 isolates. Relatedness analysis revealed the absence of distinct association between STs, ECs, LIPI-3 and LIPI-4 distribution and specific food groups. This study provided fundamental data for Chinese food safety authorities to grasp the contamination status of L. monocytogenes in foods, assess the potential risk of this pathogen and further address the safety issue of retail foods in bulk in China.